Degenerative Spinal Deformity. (October 2015) - Ailon, Tamir; Smith, Justin S.; Shaffrey, Christopher I.; Lenke, Lawrence G.; Brodke, Darrel; Harrop, James S.; Fehlings, Michael; Ames, Christopher P.
Abstract : Degenerative spinal deformity afflicts a significant portion of the elderly and is increasing in prevalence. Recent evidence has revealed sagittal plane malalignment to be a key driver of pain and disability in this population and has led to a significant shift toward a more evidence-based management paradigm. In this narrative review, we review the recent literature on the epidemiology, evaluation, management, and outcomes of degenerative adult spinal deformity (ASD). ASD is increasing in prevalence in North America due to an aging population and demographic shifts. It results from cumulative degenerative changes focused in the intervertebral discs and facet joints that occur asymmetrically to produce deformity. Deformity correction focuses on restoration of global alignment, especially in the sagittal plane, and decompression of the neural elements. General realignment goals have been established, including sagittal vertical axis <50 mm, pelvic tilt <22°, and lumbopelvic mismatch <±9°; however, these should be tailored to the patient. Operative management, in carefully selected patients, yields satisfactory outcomes that appear to be superior to nonoperative strategies. ASD is characterized by malalignment in the sagittal and/or coronal plane and, in adults, presents with pain and disability. Nonoperative management is recommended for patients with mild, nonprogressive symptoms; however, evidence of its efficacy is limited. Surgery aims to restore global spinal alignment, decompress neural elements, and achieve fusion with minimal complications. The surgical approach should balance the desired correction with the increased risk of more aggressive maneuvers. In well-selected patients, surgery yields excellent outcomes. ABBREVIATIONS: ASD, adult spinal deformity C7PL, plumb line dropped from the C7 centroid CSVL, line drawn vertically through the center of the sacrum HRQOL, health-related quality of life LL, lumbar lordosis MIS, minimally invasive surgery PA, posteroanterior PI, pelvic incidence PI − LL, lumbopelvic mismatch PJF, proximal junction failure PJK, proximal junction kyphosis PSO, pedicle subtraction osteotomy PT, pelvic tilt SRS, Scoliosis Research Society SS, sacral slope SVA, sagittal vertical axis TK, thoracic kyphosis TLIF, transforaminal lumbar interbody fusion VCR, vertebral column resection